2015
DOI: 10.1016/j.devcel.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Opposition of Clustered Proteins Stabilizes Cortical Polarity in the C. elegans Zygote

Abstract: Dynamic maintenance of cell polarity is essential for development and physiology. Here we combine experiments and modeling to elucidate mechanisms that maintain cortical polarity in the C. elegans zygote. We show that polarity is dynamically stabilized by two coupled cross-inhibitory feedback loops: one involves the oligomeric scaffold PAR-3 and the kinase PAR-1; the other involves CDC-42 and its putative GAP CHIN-1. PAR-3 and CDC-42 are both required locally to recruit PAR-6/PKC-3, which inhibits PAR-1 (shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
157
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(164 citation statements)
references
References 58 publications
(90 reference statements)
7
157
0
Order By: Relevance
“…Prior studies have suggested that PAR-3 oligomerization may contribute to maintenance of stable PAR domains during polarity maintenance phase (Dawes and Munro, 2011; Sailer et al, 2015). However, we observed that the largest PAR-3 oligomers were present during establishment phase rather than maintenance phase (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have suggested that PAR-3 oligomerization may contribute to maintenance of stable PAR domains during polarity maintenance phase (Dawes and Munro, 2011; Sailer et al, 2015). However, we observed that the largest PAR-3 oligomers were present during establishment phase rather than maintenance phase (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…The PAR domains are persistent in the polarized zygote even though individual PAR proteins undergo both lateral diffusion within the cortex and continual exchange between the cortex and the cytoplasm (Cheeks et al, 2004; Goehring et al, 2011a; Nakayama et al, 2009; Robin et al, 2014; Sailer et al, 2015). The maintenance of stable PAR domains depends on a combination of mechanisms that control where they are recruited to the cell cortex and that counteract their lateral diffusion within the cortex.…”
Section: Asymmetric Division Of the C Elegans Zygotementioning
confidence: 99%
“…During polarity maintenance, the recruitment of PAR-6/aPKC from the cytoplasm to the cortex depends on interactions with both PAR-3 and the active form of the small GTPase, CDC42 (Aceto et al, 2006; Gotta et al, 2001; Kay and Hunter, 2001). Both PAR-3 and active CDC42 are concentrated at the anterior cortex, resulting in PAR-6 cortical recruitment rates that are ~9 times higher in the anterior than the posterior cortex (Sailer et al, 2015). This dramatic asymmetry in cortical PAR-6 recruitment depends on two mechanisms that prevent PAR-3 and active CDC42 from localizing to the posterior cortex (Figure 2A).…”
Section: Asymmetric Division Of the C Elegans Zygotementioning
confidence: 99%
See 2 more Smart Citations